Password Security & User Access: Is Human Negligence the Weakest Point in Accounting Information Systems - Ahmad Arif Aufar; Widanti Retno Palupi; Rina Tjandrakirana DP (Escalate : Economics and Business Journal, 2026)
Currently in the digital era, Accounting Information Systems play an important role in managing confidential financial data. This study evaluates whether human negligence is the main vulnerability in Accounting Information Systems compared to technical factors. Using the Systematic Literature Review method of several reputable national & international journals, it was found that human factors contribute up to 85% to data leaks. Major problems include poor password management, security fatigue, vulnerability to phishing, and internal access abuse. The results of the study confirm that advanced technologies such as encryption are often paralyzed due to user negligence. In conclusion, strengthening SIA security requires a holistic approach that integrates technical solutions such as Role-Based Access Control & Multi-Factor Authentication with cyber awareness training to mitigate the risk of user behavior as the system's weakest point.